Inhibition of Vaginal Lactobacilli by a Bacteriocin-Like Inhibitor Produced by Enterococcus faecium 62-6: Potential Significance for Bacterial Vaginosis - Maureen C. Kelly; Michael J. Mequio; Vivien Pybus (Hindawi Limited, 2003)
Objective: Bacterial vaginosis (BV) is characterized by a shift in vaginal tract ecology, which includes a decrease in the concentration and/or prevalence of facultative lactobacilli. Currently, mechanisms which could account for the disappearance of lactobacilli are not well understood. The objective of this study was to determine whether vaginal streptococci/enterococci can produce bacteriocin-like inhibitors antagonistic to vaginal lactobacilli.